Application of ISA –DAC – Instrumentation Software and Data Acquisition System for Foundation Industry - Naveen Gopal; P. Rajalakshmy (Research Highlights in Science and Technology Vol. 6, 2023)
This chapter highlights about research and development of ISA –DAC – instrumentation software application and data acquisition system for the foundation industry. The Data Acquisition system would be controlled by a desktop computer running the control software (ISA), which converts raw sensor data into engineering units. During the test, on-screen data will be available to allow the results to be evaluated. The system interfaces with the latest fourth generation technology of Jack Cell testing with Instrumentation Software and Data Acquisition Systems. The system supports different types of engineering units and reports for the research studies. For maximum accuracy, the system will be linked to high resolution geotechnical instruments. The system’s unique features include data processing at various engineering units, remote monitoring via web services, online monitoring, Telemetry alert information, and graphical representation of data. In addition, the new system is expected to have an increased scope, time saving, functionality and achieves higher degree of automation.